Testing the Validity of Laplace Model Against Symmetric Models, Using Transformed Data - Hadi Alizadeh Noughabi (Statistics, Optimization & Information Computing, 2021)
In this paper, we first present three characterizations of Laplace distribution and then we introduce a goodness of fit test for Laplace distribution against symmetric distributions, based on one of the transformations. The power of the proposed test under various alternatives is compared with that of the existing tests, by simulation. To show the behavior of the proposed test in real cases, two real examples are presented.